2010
DOI: 10.1007/s11916-010-0128-4
|View full text |Cite
|
Sign up to set email alerts
|

New Trends in the Treatment and Management of Myofascial Pain Syndrome

Abstract: Myofascial pain syndrome presents a significant physical and financial burden to society. In view of the aging demographics, myofascial pain promises to be an even greater challenge to health care in the future. Myofascial trigger points have been identified as important anatomic and physiologic phenomena in the pathophysiology of myofascial pain. While their pathophysiologic mechanisms are still unclear, emerging research suggests that trigger points may be initiated by neurogenic mechanisms secondary to cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 43 publications
2
56
0
3
Order By: Relevance
“…32 It has also recently been demonstrated that localized mechanical pain hypersensitivity over ankle ligaments and the lateral malleolus exists in individuals with lateral ankle sprains. 26 This suggests that the peripheral sensitization secondary to the acuteness of the injury postlateral ankle sprain may be positively affected by myofascial techniques.…”
Section: Discussionmentioning
confidence: 99%
“…32 It has also recently been demonstrated that localized mechanical pain hypersensitivity over ankle ligaments and the lateral malleolus exists in individuals with lateral ankle sprains. 26 This suggests that the peripheral sensitization secondary to the acuteness of the injury postlateral ankle sprain may be positively affected by myofascial techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently applied techniques for TrP deactivation are spray and stretch, TrP pressure release, and local injection (see [7,17] for a more detailed description of these and other techniques). The latter represents the gold standard; it can consist of "dry needling" or injection of active substances, particularly local anesthetics.…”
Section: Management Of Trigger Pointsmentioning
confidence: 99%
“…The most recommended medical therapies include analgesics, non-steroidal anti-inflammatory drugs, myorelaxants and tricyclic antidepressants, anxiolytics and anticonvulsants (6,7).…”
Section: Pharmacologic Treatment Of Myofascial Painmentioning
confidence: 99%
“…In addition, diclofenac patches on the trigger points in the trapezius muscle were associated with improved clinical scores (9). Furthermore, short-term muscle relaxants may be used in patients with typical manifestations of MPS along with generalized muscle spasms (7). In a study investigating the efficacy of thiocolchicoside ointment or thiocolchicoside injections, the authors reported that both management modalities were effective alternatives in the management of MPS (10).…”
Section: Pharmacologic Treatment Of Myofascial Painmentioning
confidence: 99%